Treatment of keratinocyte carcinoma in elderly patients – a review of the current literature. (30th March 2020) - Leus, A.J.G.; Frie, M.; Haisma, M.S.; Terra, J.B.; Plaat, B.E.C.; Steenbakkers, R.J.H.M.; Halmos, G.B.; Rácz, E.
Abstract: A large percentage of the patients with keratinocyte carcinoma (KC, formerly known as non‐melanoma skin cancer) is of advanced age and often too frail for standard therapies. However, no specific treatment recommendations are given for this population. This review aimed to give an overview of the current literature on the best practice for the treatment of elderly patients with KC. A literature search was performed in MEDLINE, using 'keratinocyte carcinoma', 'elderly', 'treatment' and various synonyms. Case reports, reviews, comments, non‐English literature and studies with a sample size <15 were excluded. After selection, a total of 47 studies were reviewed. Two types of studies were identified, focusing on (I) the effect of age on treatment outcomes and (II) alternative treatment schedules for elderly patients. Studies on surgery, the gold standard, describe larger lesions and defect size in the elderly population. Recurrence rate, complication rate and disease‐specific survival were not affected by age. Depending on the expected morbidity of a suggested (re‐)excision and patient preferences, a conservative watchful waiting policy can be agreed upon as a shared decision. Other common treatment modalities, such as adjuvant radiotherapy, photodynamic therapy and systemic therapy for basal cell carcinoma (BCC), show comparable results in the elderly and younger population. Alternative treatment schedules for elderly patients include primary hypofractionated radiotherapy, which seems effective and well‐tolerated, although research is limited to case series. Additionally, localized and topical treatments seem safe and effective especially for low‐risk tumours. Data are lacking on the efficacy of systemic therapies of metastatic KC in elderly patients. Efficacy of most treatments (with the exception of photodynamic therapy) is not dependent on age. There is need for more research on the efficacy of adjusted treatment modalities, such as hypofractionated radiotherapy and palliative or curative systemic treatment.